2002
DOI: 10.1542/peds.110.4.e49
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Admission Rates of Children With Bronchiolitis by Pediatric and General Emergency Departments

Abstract: ABSTRACT. Objective. It is uncertain whether pediatric and general emergency departments have different admitting practices regarding children with bronchiolitis. The objective of this study was to quantify the differences in admission practices between pediatric and general emergency departments of children with bronchiolitis in 1 North American metropolitan area, controlling for various factors such as clinical severity, comorbid conditions, and socioeconomic status.Design. Retrospective cohort review of eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 50 publications
2
55
0
3
Order By: Relevance
“…25 The use of systemic corticosteroids for ED patients was similar to studies that have included community EDs within their study population. 6,26 Among inpatients, corticosteroid use was double that reported at pediatric centers. 27 The majority of trials and systematic reviews available at the time of our cohort and the AAP practice guideline did not suggest a benefit of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 The use of systemic corticosteroids for ED patients was similar to studies that have included community EDs within their study population. 6,26 Among inpatients, corticosteroid use was double that reported at pediatric centers. 27 The majority of trials and systematic reviews available at the time of our cohort and the AAP practice guideline did not suggest a benefit of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Admission rates have between reported at 13% among a cohort of patients treated at either a pediatric or a general hospital, 39 at 31% among a cohort treated at pediatric emergency departments, 9 and at 37% among a cohort treated at a general hospital. 26 The variation may reflect differences in illness severity as well as differences in physician comfort in managing bronchiolitis. 26 Two other cohort studies have also reported how commonly children return to the ED for ongoing bronchiolitis symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these were relatively small and entirely in kind. [41][42][43] From this effort, we have learned that guideline implementation can be successful even in a busy setting such as the ED. More important, we found that provider buy-in is crucial to successful implementation.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many bronchiolitis management decisions are made subjectively [2,10]. This leads to significant practice variation, as is reflected in variable admission rates and use of specific therapies among different hospitals and physicians [1,4,[10][11][12][13][14][15][16][17][18][19][20]. Observed practice variation is not explained by differences in patient severity and has little impact on outcomes, but has a significant impact on healthcare resource usage [17].…”
Section: Introductionmentioning
confidence: 99%